REVERSIBLE CELLULAR AUTOMATA WITH PENTA-CYCLIC RULE AND ECCs - Siap, Irfan; Akin, Hasan; Koroglu, Mehmet E. (WORLD SCIENTIFIC PUBL CO PTE LTD, 2012)
The reversibility problem for linear cellular automata with null boundary defined by a rule matrix in the form of a pentadiagonal matrix was studied over the binary field Z(2) by Martin del Rey et al. [Appl. Math. Comput. 217, 8360 (2011)]. Recently, the reversibility problem of 1D Cellular automata with periodic boundary has been extended to ternary fields and further to finite primitive fields Z(p) by Cinkir et al. [J. Stat. Phys. 143, 807 (2011)]. In this work, we restudy some of the work done in Cinkir et al. [J. Stat. Phys. 143, 807 (2011)] by using a different approach which is based on the theory of error correcting codes. While we reestablish some of the theorems already presented in Cinkir et al. [J. Stat. Phys. 143, 807 (2011)], we further extend the results to more general cases. Also, a conjecture that is left open in Cinkir et al. [J. Stat. Phys. 143, 807 (2011)] is also solved here. We conclude by presenting an application to Error Correcting Codes (ECCs) where reversibility of cellular automata is crucial.
Keywords: Cellular automata; periodic boundary condition; reversibility; matrix representations; ECCs; BLOCK CIPHER; BEHAVIOR; Computer Science; Physics